The association between poor oral hygiene and infective endocarditis risk in rheumatic heart disease patients: a systematic review - Amiria, Farah; Aini Gumilas, Nur Signa (Universitas Padjadjaran, 2025)
Introduction: Infective endocarditis (IE) is a heart condition that may result from subacute bacterial infections. One cause of IE is oral bacterial infections, particularly Streptococcus species, which enter the blood vessels through injured gingiva during tooth brushing or dental procedures. Rheumatic heart disease (RHD) is a major predisposing factor in developing countries, with viridans streptococci implicated in its etiology. This background highlights the importance of maintaining oral hygiene, especially in RHD patients, to reduce the risk of IE. This systematic review aims to investigate the association between poor oral hygiene and the risk of IE in patients with RHD. Method: A systematic review was conducted in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Articles published between 2014 and 2024 were sourced from PubMed, Scopus, and Google Scholar using specific keyword combinations related to IE, RHD, and oral health. Inclusion and exclusion criteria were applied based on the PECO framework. Results: A total of four eligible studies were identified. The findings suggest that RHD patients with poor oral hygiene are more vulnerable to developing IE due to an increased risk of bacteremia originating from oral infections. Conclusion: Poor oral hygiene is associated with an increased risk of infective endocarditis in patients with rheumatic heart disease. Bacterial adherence to damaged heart valves can lead to biofilm formation and vegetations, increasing the likelihood of infection. Preventive dental care and appropriate prophylactic measures should be prioritized in this high-risk population to reduce disease burden.